The Process of Change in the Sexual Attitudes of Sexual Offenders in Korea - Boksun Yang, RN, PhD; Okhee Ahn, RN, PhD (Elsevier, 2007)
This study aimed to explore the process of change in the sexual views and attitudes of sexual offenders, in light of their experiences. Methods: Data were collected from six sexual offenders who were accused of sexual offenses. All collected data by in-depth and direct observation were analyzed by Corbin and Strauss' Ground theory methodology. Results: Participants were sexually aroused as a result of their distorted knowledge of sex. They were stimulated by easy access to sex and surrendered to it. Their intervening conditions were legal regulation, voice of conscience and social support. Participants were responding to the problem through strategies. These strategies were: reflecting self, distracting one's attention, and building a stable relationship with a woman. They resulted in stigma of being a sexual offender, alteration in sexual views, confidence and futility. The core variable revealing the essence of the sexual offenders' experiences was reconstructing sound sex values. Conclusion: The results of the study can provide school nurses and sex educators with useful knowledge grounded in actual sexual offense cases, not only to refine the interventions for sexual offenders but also to prevent future sexual offenses.